2018
DOI: 10.3168/jds.2017-14305
|View full text |Cite
|
Sign up to set email alerts
|

Considering milk price volatility for investment decisions on the farm level after European milk quota abolition

Abstract: After the abolition of the milk quota in the European Union, milk price volatility is expected to increase because of the liberalized market conditions. At the same time, investment appraisal methods have not been updated to capture the increased uncertainty. Therefore, the objective of this paper is to assess the effect of changing price volatility due to quota abolition on investment decisions at the dairy farm level. To contribute to the objective and to approximate milk price volatility after the European … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 33 publications
0
29
0
1
Order By: Relevance
“…The removal of milk quotas significantly changed the dairy business environment. Dairy farmers have started to face considerable milk price volatility, which affects their production and investment decisions [1,[20][21][22]. New business strategies have also changed the dairy sector structure (i.e., the number of farms and farm size distribution) [23].…”
Section: Of 21mentioning
confidence: 99%
“…The removal of milk quotas significantly changed the dairy business environment. Dairy farmers have started to face considerable milk price volatility, which affects their production and investment decisions [1,[20][21][22]. New business strategies have also changed the dairy sector structure (i.e., the number of farms and farm size distribution) [23].…”
Section: Of 21mentioning
confidence: 99%
“…If a farm has sufficient funds of its own or might be able to provide the necessary assets as collateral (e.g., by owned land), it might still refrain from investment if a combination of additional loan payments and increased price volatility puts the future liquidity of the farm at risk. Schulte et al (2018) showed that increased milk price volatility can considerably affect the profitability of investment decisions if farmers are risk-averse. A negative effect of milk price volatility on the investment propensity of dairy farms was confirmed by Zimmermann and Heckelei (2012) for a dataset on European farms.…”
Section: Related Literaturementioning
confidence: 99%
“…It is difficult to match the agricultural technology services with the technical needs of the farmers effectively, which is reflected in the farmers' relatively blind choice and adjustment behavior in grain production investment. Due to the differences in natural resource endowments, economic and social foundations, scale of operations, and farmers' conditions, the farmers' investment adjustment behavior varies significantly [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…A variety of research methods were used in previous research to study farmers' investment adjustment behavior from different perspectives. For example, Factor Analysis [3,7], Multinomial Logit Model [8,10,11], Deterministic Discrete Event Model [9], Mixed Logit Model with Flexible Mixing Distribution [12], Tobit Model [13,14], Probit Model [15][16][17], and Structural Equation Modeling [18,19].…”
Section: Introductionmentioning
confidence: 99%